Remnant oyster reefs as fish habitat within the estuarine seascape. (July 2022) - Martínez-Baena, Francisco; Lanham, Brendan S.; McLeod, Ian M.; Taylor, Matthew D.; McOrrie, Stephen; Luongo, Alyssa; Bishop, Melanie J.
Abstract: Interest in oyster reef conservation and restoration is growing globally, but particularly in Australia, it is unclear the extent to which oyster reefs complement (versus replicate) habitat provisioning by other structured habitats in the seascape. Remote underwater video surveys of two east Australian estuaries revealed that at high tide, oyster reefs not only supported distinct fish communities to bare sediments but also to adjacent seagrass beds and mangrove forests. Fish observations in oyster reefs were close to double that of mangroves and seagrass, with species richness, abundance, feeding and wandering behaviours similar. Several species of blenny and goby were unique to oyster reefs and oyster-containing mangroves, whilst recreationally fished species such as bream and mullet were more abundant on oyster reefs than in other habitats. Resolving the association between oyster reefs and fish species within the broader seascape will assist in developing restoration and management strategies that maximise fisheries benefit. Highlights: The role of intertidal remnant oyster reefs as fish habitat was explored. Oyster reefs provided habitat to a unique fish community within the seascape. Fish observations were higher in oyster reefs, than in seagrass, mangroves and bare. Fish sp. richness was higher in oyster reefs, than in seagrass, mangroves and bare. Oyster reefs were utilised as refuge and foraging grounds by fish.